SUBSITUSI TEPUNG JAGUNG DAN TERIGU DALAM PEMBUATAN MIE GORENG - Hikmathine Osella Putri (Jurnal Kesehatan, 2023)
In Indonesia, many types of noodles have been spread, especially in wet noodles, fried noodles and instant noodles. It is most likely that the basic ingredient for making these noodles is wheat flour which has been imported from abroad, therefore this research aims to utilize corn flour as a substitute for flour. flour in the manufacture of fried noodles. In the process of making noodles, in general, it requires various additional ingredients that have specific purposes, such as shape or volume. Other additional ingredients used for making noodles are salt, water, eggs, and wheat flour. Corn has health benefits for our bodies with its nutritional value. Apart from preparing various dishes, this corn can also be used to make corn milk. Apart from being a delicious drink, corn milk has many health benefits, because milk made from corn will be rich in vitamin E and can help soften and make our skin brighter, as well as B vitamins which help maintain healthy nerves. Daily consumption of milk is one way to combat weight loss (Anonymous, 2019).